Upaya Pemahaman Materi Haid dan Istihadhah Melalui Pengkajian Kitab Risalatul Mahid di Pondok Pesantren Hidayatul Mubtadiin Sidoharjo Jati Agung Lampung Selatan - Nur Fadhila; Weni Kurniawati; Finy Muslihatuzzahro (Journal on Education, 2024)
This research aims to find out how efforts are made to understand menstruation and istihadhah material through studying the book Risalatul Mahid at the Hidayatul Mubtadiin Islamic Boarding School. This problem was discussed through field study research carried out at the Hidayatul Mubtadiin Islamic Boarding School with 6 respondents, namely 1 ustadz, 1 female village head, 1 female administrator and 3 female students. Data collection methods use observation, interviews and documentation methods. Data was obtained by asking questions through an interview process. This interview was conducted with all respondents and also teachers who taught the book Risalatul Mahid. All data was analyzed using a qualitative descriptive approach. Based on research conducted on female students at the Hidayatul Mubtadiin Sidoharjo Jati Agung South Lampung Islamic boarding school, it was concluded that overall the female students' understanding of menstruation and istihadhah was quite good. This can be seen from the results of interviews conducted with santri, ustadz, female village heads, as well as menstrual journal section administrators. They understand more or less the material about menstruation and istihadhah taught in the Risalatul Mahid book. However, there is also some material that still confuses them, such as the various types of menstrual blood, how to make up for prayers missed during menstruation, how to punish istihadhah blood and so on.